Frequency of But Not Capacity for Participation in Everyday Activities Is Associated With Cognitive Impairment in Late Life. (November 2021) - Wu, Chao-Yi; Rodakowski, Juleen; Terhorst, Lauren; Dew, Mary Amanda; Butters, Meryl; Karp, Jordan F.; Albert, Steven M.; Gildengers, Ariel G.; Reynolds, Charles F.; Skidmore, Elizabeth R.
We examined features of everyday activities (capacity and frequency) between older adults with and without cognitive impairment over 12 months. Participants aged ≥60 years and at risk for depression were included (n = 260); 26% ( n = 69) had an acquired cognitive impairment at baseline. Cognitive impairment was defined as one standard deviation below norms on the Repeatable Battery for the Assessment of Neuropsychological Status. Features of everyday activities were measured by a computerized adaptive test version of Late-Life Function and Disability Instrument (LLFDI) at six time points (baseline, 6 weeks, 3, 6, 9, 12 months). There were significant between-group differences in activity frequency ( p = .04), but not activity capacity ( p = .05). The group difference in activity frequency exceeded minimal detectable changes (MDC90 = 3.7) and reached moderate clinical meaningfulness (∆ at six time points = 3.7–4.7). Generalized linear mixed models revealed no Group × Time interactions on activity capacity and frequency ( p = .65 and p = .98). Practitioners may assess changes in activity frequency to monitor cognitive status of clients even when there is no loss of activity capacity.